2022
DOI: 10.1136/bmjsem-2021-001165
|View full text |Cite
|
Sign up to set email alerts
|

Declining fitness and physical education lessons in UK adolescents

Abstract: ObjectivesThe objective was to determine recent cross-sectional trends in health-related fitness (HRF) in secondary school students by studying the 13–14 years old age group repeatedly over 6 years, considering parallel national trends in physical education (PE).MethodsHeight, weight, broad jump, grip strength, 20 m shuttle run and throwing and catching skills were measured by the same research team using standardised techniques from 2014 to 2019. Trends in these HRF measures were assessed by linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Given the worsening CRF of children and adolescents, [20][21][22] recommendations about the intensity and duration of PA required to reverse this trend are urgently needed and should be based on robust evidence. As guidelines are currently based on combined MVPA targets, we consider this an important aim.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Given the worsening CRF of children and adolescents, [20][21][22] recommendations about the intensity and duration of PA required to reverse this trend are urgently needed and should be based on robust evidence. As guidelines are currently based on combined MVPA targets, we consider this an important aim.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Other studies, in addition to highlighting significant lower physical fitness measures (grip strength, standing long jump, 20-meter shuttle run) and motor competence (throwing and catching skills) in schoolchildren aged 13-14 years from 2014 to 2019, reported the reduction of the 16% of the hours spent in physical education between 2010 and 2019 [40]. Data revealed that the normal-weight group has highlighted the most important decline in fitness levels and motor competence compared to the overweight-obese peers [41].…”
Section: Discussionmentioning
confidence: 96%
“…It is widely reported that school-aged children have progressively worse physical fitness [ 73 ]. Due to limited time for a physical education class, leisure activities, adapting unhealthy dietary habits, and increased sedentary behavior (exposure to screens) resulting in excess body weight [ 13 , 74 ]. Obesity is also associated with decreased physical and motor abilities in school-aged children [ 72 , 75 , 76 ], specifically those living in rural areas [ 31 , 35 , 56 ].…”
Section: Discussionmentioning
confidence: 99%